2010
DOI: 10.1021/ic9021799
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of the Mechanism in Fluorine-Free Prepared YBa2Cu3O7−δ Coatings

Abstract: In this work, the reaction mechanism used in the preparation of fluorine-free superconducting YBa(2)Cu(3)O(7-delta) (YBCO) was investigated. To determine which precursor interactions are dominant, a comprehensive thermal analysis (thermogravimetric analysis-differential thermal analysis) study was performed. The results suggest that a three step reaction mechanism, with a predominant role for BaCO(3), is responsible for the conversion of the initial state to the superconducting phase. In the presence of CuO, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
50
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 37 publications
7
50
0
Order By: Relevance
“…The development of water-based fluorine-free prepared YBCO coatings can be tremendously boosted if a realistic reaction model is coupled to an appropriate modelling of the thermal process. In a previous paper, the reaction mechanism was cleared out with a predominant role for BaCO 3 [22]. In this paper, we combine this reaction mechanism with all observations concerning a change in the thermal process, more specifically in sinter atmosphere and sinter temperature.…”
Section: Introductionmentioning
confidence: 85%
“…The development of water-based fluorine-free prepared YBCO coatings can be tremendously boosted if a realistic reaction model is coupled to an appropriate modelling of the thermal process. In a previous paper, the reaction mechanism was cleared out with a predominant role for BaCO 3 [22]. In this paper, we combine this reaction mechanism with all observations concerning a change in the thermal process, more specifically in sinter atmosphere and sinter temperature.…”
Section: Introductionmentioning
confidence: 85%
“…4a) observed in the case of the YBCO film pyrolized at 600 for 30 min. Literature studies [14] have demonstrated that the reaction between BaCO 3 and CuO takes place with the formation of the BaCuO 2 phase. This observation is a first indication of the importance of the pyrolysis dwell time during the thermal treatment.…”
Section: Resultsmentioning
confidence: 99%
“…The main disadvantage of the TFA-MOD is the long duration of the pyrolysis step that limits the overall production rate and the liberation of highly corrosive and toxic HF during the YBCO crystallization step. To overcome this disadvantage, several research groups are trying to reduce the fluorine content using low-fluorine [9][10][11][12], and fluorinefree coating solutions [13,14] starting from different precursors and solvents, which can avoid the HF formation. Metal acetates, acetylacetonates, nitrates and triethanolamine, ethylene glycol, propionic acid chelating agents were used for the preparation of the precursor coating solutions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here it would be appropriate to say that some useful information about the thermal decomposition behaviour properties and the role of other BaCO 3 and CuO precursors can be obtained, e.g. [17]. Thereafter, the powders were carefully weighed in appropriate weight amounts, manually homogenized in acetone in an agate mortar for five minutes, put into alumina…”
Section: Methodsmentioning
confidence: 99%